Growth and Yield Characters of Potato Genotypes Grown in Drought and Irrigated Conditions of Nepal - Luitel, Binod Prasad; Khatri, Bhim Bahadur; Choudhary, Duryodhan; Paudel, Bishnu Prasad; Jung-Sook, Sung; Hur, On- Sook; Baek, Hyung Jin; Cheol, Ko Ho; Yul, Ryu Kyoung (International Journal of Applied Sciences and Biotechnology, 2015)
This experiment was conducted to assess the genotypic variation for the growth, yield and yield components of potato grown under drought and irrigated conditions at Hattiban Research Farm, Khumaltar during the summer cropping season (Feb.-May) of the two consecutive years (2013 and 2014). The results revealed that canopy cover, stem height and number of leavers were more sensitive to drought and the effect was more pronounced in early cultivar Desiree. Stem height and leaf number of plant were more (36% and 45%, respectively) reduced in Desiree than other genotypes. Mean tuber number decreased by 55% under drought condition. Drought stress reduced marketable tuber number by 79% as compared to irrigated treatment. Drought stress reduced the marketable tuber yield from 70% to 87%. The clones CIP 392242.25 and LBr-40 had relatively lower yield loss, and less drought susceptibility index under drought indicating their tolerance to drought in field condition. Further experiment is recommended to study the physiological parameters of these genotypes under different water and soil conditions. Int J Appl Sci Biotechnol, Vol 3(3): 513-519